2016
DOI: 10.1111/jwas.12312
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thyroxin and Domperidone on Oocyte Maturation and Spawning Performances in the Rabbit Fish, Siganus guttatus

Abstract: Thyroxin (T4) is proven to have various functions in fish reproduction. In this study, we investigated oocyte maturation and spawning performance in the rabbit fish, Siganus guttatus, orally exposed to different doses of T4 (0.05, 0.25, and 0.5 mg/kg fish) during vitellogenesis. No statistically significant differences of reproductive characteristics were observed among the treatments. However, the group that was exposed to the dose of 0.5 mg/kg spawned after receiving a hormone injection. The findings suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Linard et al (1995) and Saligaut et al (1999) (Sukumasavin, Sakulthong, & Sangthong, 2000) and in the crucian carp C. carassius (Cejko & Kucharczyk, 2015) substantiating the inhibitory role for DA. However, treatment with DA antagonist domperidone during early stages of reproductive cycle did not induce oocyte maturation and spawning in the rabbitfish Siganus guttatus (Hung & Hoang, 2016). These results suggest that the action of DA might be dependent on the stage of reproductive cycle in fish.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Linard et al (1995) and Saligaut et al (1999) (Sukumasavin, Sakulthong, & Sangthong, 2000) and in the crucian carp C. carassius (Cejko & Kucharczyk, 2015) substantiating the inhibitory role for DA. However, treatment with DA antagonist domperidone during early stages of reproductive cycle did not induce oocyte maturation and spawning in the rabbitfish Siganus guttatus (Hung & Hoang, 2016). These results suggest that the action of DA might be dependent on the stage of reproductive cycle in fish.…”
Section: Discussionmentioning
confidence: 78%
“…In teleosts, the ovarian activity is synchronized by the hormones produced by the BPG-axis (Nagahama, 1997 & Chang, 1986), the tilapia O. mossambicus (Yaron et al, 2003) and the zebra fish Danio rerio (Fontaine et al, 2013). However, treatment with DA antagonist domperidone during early stages of reproductive cycle did not induce oocyte maturation and spawning in the rabbitfish Siganus guttatus (Hung & Hoang, 2016). However, treatment with DA antagonist domperidone during early stages of reproductive cycle did not induce oocyte maturation and spawning in the rabbitfish Siganus guttatus (Hung & Hoang, 2016).…”
Section: Discussionmentioning
confidence: 94%
“…Similarly, a recent study showed that the treatment to female gold sh (Carassius auratus) with T 3 resulted in an increase of VTG [9]. In contrast, rabbit sh (Siganus guttatus) fed T 4 during vitellogenesis did not advance oocyte maturation, but could induce spawning [23]. Moreover, in female S. trutta from a wild strain, the increase in plasma THs around the time of ovulation had an in uence on nal maturation of oocytes, while the absence of any appreciable change in pro le of T 4 indicated that the increase of THs are not necessary for ovarian maturation in cultured strain [12].…”
Section: Discussionmentioning
confidence: 87%
“…Gonadotropins such as follicle-stimulating hormone (FSH) and luteinizing hormones (LH) regulate the biosynthesis of sex steroids that subsequently control the processes of sexual behavior and spermation/ovulation (Nagahama & Yamashita, 2008;Schulz et al, 2010;Zohar, Munoz-Cueto, Elizur, & Kah, 2010). hCG and D-Ala 6 , Pro 9 -Net-mGnRH are exogenous hormones that have been used separately or in combination for fish reproduction in many parts of Asia (Ayson, 1991;Komatsu, Bhandari, Kobayashi, Nakamura, & Nakamura, 2006;Marte, 1989;Pham & Le, 2016;Pham, Nguyen, Nguyen, & Arukwe, 2010). These exogenous hormones have been shown to improve maturation, ovulation and spawning performance in both wild and cultured fish species (Pham et al, 2010;Rahman, Takemura, & Takano, 2002;Zadmajid, 2016;Zadmajid, Bashiri, Sharafi, & Butts, 2018).…”
mentioning
confidence: 99%